COVID-19: A Potential Trigger for Thyroid Dysfunction - Ashraf, Sohaib (Am J Med Sci, 2021)
Subacute thyroiditis (SAT) is a self-limiting thyroid dysfunction of viral origin. Relatively little is known about its occurrence in SARS CoV-2 infected COVID-19 patients. Herein, we report a case of SAT in a 58-year-old patient that was apparently triggered by infection with SARS CoV-2. Clinical, laboratory and imaging features of the patient are presented. The patient was vitally stable with a slightly tender and warm thyroid gland, which was painful on swallowing. His free thyroxine (FT4) was elevated, thyroid stimulating hormone (TSH) was below normal and free triiodothyronine (FT3) was in the physiological range. Previous thyroid exam conducted as a part of routine annual physical checkup was normal. The patient was put on prednisolone and recovered completely within three weeks.